+0  
 
0
35
1
avatar+59 

simplify

options for the answer are:

cos^2 θ

-sin^2 θ

-cos^2 θ

sin^2 θ

 May 3, 2020
 #1
avatar+111326 
+1

I;m using x  instead of theta  (it doesn't matter )

 

Note  that      sin (-x)  = - sin (x)     and  sec (-x )  =  sec (x)

 

sin (-x) tan (x)        - sin (x) sin x / cos x           - sin^2 x

___________   =  __________________  =   ____________   =  - sin^2 x

  sec (-x)                       sec (x)                          (1/cos x) cos x

 

 

cool cool cool

 May 3, 2020

23 Online Users

avatar